Muscle FOXO-Specific Overexpression and Endurance Exercise Protect Skeletal Muscle and Heart from Defects Caused by a High-Fat Diet in Young Drosophila. - Jin, J.H.; Wen, D.T.; Chen, Y.L.; Hou, W.Q. (Frontiers in bioscience (Landmark edition), 2023)
Obesity appears to significantly reduce physical activity, but it remains unclear whether this is related to obesity-induced damage to skeletal muscle (SM) and heart muscle (HM). Endurance exercise (EE) reduces obesity-induced defects in SM and HM, but its molecular mechanism is poorly understood. The UAS/GAL4 system was used to construct the regulation of SM-specific FOXO gene expression in Drosophila, and the transgenic drosophila was subjected to EE and high-fat diet (HFD) intervention. The structure and function of SM and HM were impaired by a HFD and muscle-FOXO-specific RNAi (MFSR), including reduced climbing speed and climbing endurance, reduced fractional shortening of the heart, damaged myofibrils, and reduced mitochondria in HM. Besides, a HFD and MFSR increased triglyceride level and malondialdehyde level, decreased the Sirt1 and FOXO protein level, and reduced carnitine palmityl transferase I, superoxide dismutase, and catalase activity level, and they dow-regulated FOXO and bmm expression level in SM and HM. On the contrary, both muscle FOXO-specific overexpression (MFSO) and EE prevented abnormal changes of SM and HM in function, structure, or physiology caused by HFD and MFSR. Besides, EE also prevented defects of SM and HM induced by MFSR. Current findings confirmed MFSO and EE protected SM and heart from defects caused by a HFD via enhancing FOXO-realated antioxidant pathways and lipid catabolism. FOXO played a vital role in regulating HFD-induced defects in SM and HM, but FOXO was not a key regulatory gene of EE against damages in SM and HM. The mechanism was related to activity of Sirt1/FOXO/SOD (superoxide dismutase), CAT (catalase) pathways and lipid catabolism in SM and HM.